Preliminary survey on the crucial root causes of material waste generation in Malaysian construction industry - Nagapan, Sasitharan; Kaliannan, Suaathi; Abdullah, Abd Halid; Sohu, Samiullah; Deraman, Rafikullah; Hasmori, Muhammad Fikri; Abas, Nor Haslinda (Engineering, Technology and Applied Science Research (ETASR), 2018)
Construction waste generation has been perceived as a crucial issue that has critical consequences on the project effectiveness and ecological effect of the construction industry. The key objective of the current research is to identify the root causes of material construction waste generation in Malaysia. A well-structured questionnaire was designed based on the 52 identified root causes of material waste generation. The developed questionnaire was distributed to 35 highly experienced in Malaysian construction industry experts. The collected data was analyzed by the use of mean score analysis. The top identified root causes are poor supervision during the construction stage, lack of efficient site management, last minute changes, cutting uneconomical sizes of materials, and constant design changes during the construction period. The initial findings will aid construction practitioners to focus on these root causes in order to reduce the material construction waste generation at construction sites.